2017
DOI: 10.1080/01612840.2017.1341587
|View full text |Cite
|
Sign up to set email alerts
|

Working with Families Affected by Mental Distress: Stakeholders' Perceptions of Mental Health Nurses Educational Needs

Abstract: AcknowledgementsThis project has been funded with support from the European Commission/ Life-long learning programme. This publication reflects the views only of the authors, and the Commission cannot be held responsible for any use, which may be made of the information contained therein. 2 AbstractFamily and informal caregivers provide a substantial amount of care and support to people who experience mental health problems. The aim of this study was to explore mental health nurses', students' and service user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…This is one of few studies to examine factors influencing quality of FCC perceived by primary family caregivers of patients with schizophrenia. Findings of our study extend previous work on families’ and MHNs’ experiences of engagement around care planning within mental health services (Doody et al, ; Keogh et al, ; Wong, ). Findings from this study revealed that supportive attitudes of MHNs toward schizophrenia and chronic rehabilitation psychiatric wards where patients received care were key determinants of greater primary family caregivers’ perceptions of quality of FCC in relation to enabling and partnerships, provision of general and specific information, coordinated and comprehensive care, and respectful and supportive care.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is one of few studies to examine factors influencing quality of FCC perceived by primary family caregivers of patients with schizophrenia. Findings of our study extend previous work on families’ and MHNs’ experiences of engagement around care planning within mental health services (Doody et al, ; Keogh et al, ; Wong, ). Findings from this study revealed that supportive attitudes of MHNs toward schizophrenia and chronic rehabilitation psychiatric wards where patients received care were key determinants of greater primary family caregivers’ perceptions of quality of FCC in relation to enabling and partnerships, provision of general and specific information, coordinated and comprehensive care, and respectful and supportive care.…”
Section: Discussionsupporting
confidence: 85%
“…Family members generally perceived that they are blamed and alienated from the caring context without appreciation of their caretaking roles by mental healthcare providers (Cree et al, ; Eassom, Giacco, Dirik, & Priebe, ). Family engagement in care planning is fraught with issues of healthcare providers’ inadequate family nursing knowledge and skills and ethical dilemmas around confidentiality (Doody et al, ; Keogh et al, ; Skärsäter et al, ). Approximately one in three family caregivers in the study by Vermeulen et al () felt dissatisfied with the support they received from MHNs.…”
mentioning
confidence: 99%
“…Many of the people who experience mental disorders are supported by the family. [1][2][3][4] Members of a family provide a substantial quantity of care, 1,5,6 and the involvement of family members in the assistance of persons with a mental disorder is clinically relevant, because it improves the quality of the health care. 7 Know the links and the social support networks, namely the family, are facilitation strategies enlarger of mental health actions, thus, the family should be understood as a partner in facing and experiencing the mental disorder.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there was an understanding that the family was in its own essential a disease generator. 2 The paradigm change in the mental health care intended for community states that a greater emphasis should be placed on the family's involvement, 5 and this family should be considered as an indispensable social actor for care effectiveness. 2,[8][9][10] The last reform of primary healthcare in Portugal (equivalent to Primary Health Care in Brazil) had formal beginning in 2005, integrating different types of units, namely: the PHU (Public Health Unit) which works as observatory on health of the geographical area in which it is integrated; the SARU (Shared Assistance Resource Units) that integrate social workers, psychologists, physical therapists, occupational therapists, among others, and which provides assistance services to all other functional units; the CCU (Community Care Units) that provides health care and psychological and social support, in the scope of the domicile and the community; the HPCT (Home Palliative Care Teams) provides care to patients, who need them, in their home, such as, support their relatives and caregivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation